Resistance of Optogenetically Evoked Motor Function to Global Ischemia and Reperfusion in Mouse in Vivo. Issue 8 (August 2013) - Xie, Yicheng; Chen, Shangbin; Anenberg, Eitan; Murphy, Timothy H
Recently we have shown that despite reperfusion, sensory processing exhibits persistent deficits after global ischemia in a mouse in vivo model. We now address how motor output, specifically cortically evoked muscle activity, stimulated by channelrhodopsin-2 is affected by global ischemia and reperfusion. We find that the light-based optogenetic motor map recovers to 80% within an hour. Moreover, motor output recovers relatively faster and more completely than the sensory processing after 5-minute period of global ischemia. Our results suggest a differential sensitivity of sensory and motor systems to the effects of global ischemia and reperfusion that may have implications for rehabilitation.